Penatalaksanaan Holistik Wanita Usia 49 tahun dengan Tuberkulosis Paru dan Diabetes Mellitus Tipe 2 dengan Tingkat Pengetahuan Minimal dan Sikap Menjaga Kelangsungan Pengobatan melalui Pendekatan Kedokteran Keluarga - Clarisa Rahmah; Shenia Verinda Harsa; Diana Mayasari (CV. Jasa Sukses Abadi, 2023)
Infectious diseases with comorbidity are important health problems that are supposed to be evaluated immediately because they have the potential for complications if no intervention is carried out. Tuberculosis (TB) is an infectious disease that is still a problem in the world especially in developing countries. Diabetes mellitus is estimated to be the cause of 15% of tuberculosis cases today, because it could decrease the immune system which can cause someone prone to get infectious disease. The family approach in the management of Pulmonary Tuberculosis and diabetes mellitus can help identify factors that influence clinically, personally and family psychosocial so that management will be more comprehensive. This study is a case report. Primary data were obtained through history taking, physical examination, supporting examination and home visits to assess the physical environment. Prior to the intervention, the patient's knowledge about the disease was lacking, the pattern of curative treatment, diet was not good, rarely exercised. Family knowledge about Pulmonary Tuberculosis and diabetes mellitus is still low. After the intervention, there was an improvement in the knowledge score and attitude to maintan continuity of treatment which increased by 40 points. After the treatment was carried out on the patient, there was an improvement in the knowledge and attitude to maintan continuity of treatment regarding the disease, as well as an improvement in diet and physical activity patterns.